2020
DOI: 10.3389/fnmol.2020.00083
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell RNA Analysis of Type I Spiral Ganglion Neurons Reveals a Lmx1a Population in the Cochlea

Abstract: In the mature cochlea, each inner hair cell (IHC) is innervated by multiple spiral ganglion neurons of type I (SGNI). SGNIs are morphologically and electro-physiologically diverse. Also, they differ in their susceptibility to noise insult. However, the molecular underpinnings of their identity and physiological differences remain poorly understood. In this study, we developed a novel triple transgenic mouse, which enabled the isolation of pure populations of SGNIs and the analysis of a 96-gene panel via single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 77 publications
3
8
0
Order By: Relevance
“…These Prph- eGFP-positive type II cell bodies are not uniformly located throughout the spiral ganglion. Instead, these Prph- eGFP-positive cell bodies appear to be more concentrated along the distal region of the spiral ganglion ( Figures 1C–F″ ), consistent with reports using antibody labeling ( Hafidi, 1998 ; Nayagam et al, 2011 ; Defourny et al, 2013 ; Grandi et al, 2020 ). This asymmetrical distribution was better visualized with NeuN labeling of Prph- eGFP mice to label all SGN nuclei ( Figure 2A ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These Prph- eGFP-positive type II cell bodies are not uniformly located throughout the spiral ganglion. Instead, these Prph- eGFP-positive cell bodies appear to be more concentrated along the distal region of the spiral ganglion ( Figures 1C–F″ ), consistent with reports using antibody labeling ( Hafidi, 1998 ; Nayagam et al, 2011 ; Defourny et al, 2013 ; Grandi et al, 2020 ). This asymmetrical distribution was better visualized with NeuN labeling of Prph- eGFP mice to label all SGN nuclei ( Figure 2A ).…”
Section: Resultssupporting
confidence: 88%
“…As in this previous study with peripherin antibodies, once Prph-eGFP became restricted, specifically type II SGN cell bodies, they remained restricted throughout adulthood ( Figure 1 ), suggesting that Prph- eGFP is a useful marker for mature type II SGN perikarya. The unique localization to the distal region of the spiral ganglia ( Figure 2 ) has been reported ( Berglund and Ryugo, 1987 ; Hafidi, 1998 ; Nayagam et al, 2011 ; Maison et al, 2016 ; Grandi et al, 2020 ); however, we observed that this primarily distal distribution of type II SGNs was not uniform along the cochlea.…”
Section: Discussionsupporting
confidence: 40%
“…Expression in human type I spiral ganglion neurons is consistent with previous results in mice that used in situ hybridization and singlecell RNA analysis to demonstrate Lmx1a expression in a discrete type I spiral ganglion neuron subpopulation in the developing mouse cochlea [127]. These subtypes have been hypothesized to correspond to different excitation potentials thresholds [127] and enable further encoding of auditory information at the level of the spiral ganglion [128]. LMX1A encodes a transcription factor, LIM homeobox transcription factor 1-alpha, which is involved in neuronal differentiation as well as maintenance of neuronal homeostasis in the adult brain [129].…”
Section: Focal Adhesion Kinase 1 (Fak)supporting
confidence: 90%
“…Knockout of FZD2 in the mouse cochlea results in defects in OHC number and orientation, which are most severe in the apical region. In addition, a recent study identified FZD2 as a signature gene in one of three distinct SGN I populations by using single-cell transcriptome ( Grandi et al, 2020 ). In the mouse cochlea, planar polarity is guided by the PCP proteins FZD3 and FZD6.…”
Section: Roles Of Class F G Protein-coupled Receptors In Cochleamentioning
confidence: 99%